2020
DOI: 10.3390/met10070896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Sputtering Power on the Structure, Morphology and Magnetic Properties of Fe Films

Abstract: In this paper, the radio frequency (RF) magnetron sputtering (MS) method was utilized to fabricate multiple sets of the iron film samples under different sputtering powers. With the help of X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM) and vibrating sample magnetometer (VSM), how the sputtering power affected the structure, morphology and magnetic properties of the iron film was studied. XRD results showed that all Fe films have a polycrystalline bcc structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 43 publications
4
4
0
Order By: Relevance
“…Notably, this observation is also strengthened by the increase of the crystallite size with increasing the RF power (see Table 1), confirming that in given conditions, for a certain range of RF power, the crystallite size raises, while the surface roughness decreases with the sputtering power. This trend is consistent with previous studies, mentioning that at an exceedingly high RF power, the surface roughness could increase due to excessive scattering effects close to the substrate' surface that typically reduce the overall sputtering rate and favor the formation of defects and coarse grains at the surface of the sputtered films [41], effect observed in our studies, too, by an increase of R A and RMS values, i.e., to 1.3 nm and 1.6 nm, respectively, for the ZnSe film deposited at 120 W (see Table 2). Notably, the ZnSe film grown at 100 W (ZnSe3) features the smallest R A and RMS values, i.e., 0.8 nm and 1.0 nm, respectively, in respect to the rest of the fabricated samples, eventually demonstrating that the latter sputtering conditions could allow the fabrication of ZnSe thin films with lowest defects density and excellent flatness, suitable to be used as "window" or buffer layers within various solar cells architectures.…”
Section: Morphological Characterizationssupporting
confidence: 93%
“…Notably, this observation is also strengthened by the increase of the crystallite size with increasing the RF power (see Table 1), confirming that in given conditions, for a certain range of RF power, the crystallite size raises, while the surface roughness decreases with the sputtering power. This trend is consistent with previous studies, mentioning that at an exceedingly high RF power, the surface roughness could increase due to excessive scattering effects close to the substrate' surface that typically reduce the overall sputtering rate and favor the formation of defects and coarse grains at the surface of the sputtered films [41], effect observed in our studies, too, by an increase of R A and RMS values, i.e., to 1.3 nm and 1.6 nm, respectively, for the ZnSe film deposited at 120 W (see Table 2). Notably, the ZnSe film grown at 100 W (ZnSe3) features the smallest R A and RMS values, i.e., 0.8 nm and 1.0 nm, respectively, in respect to the rest of the fabricated samples, eventually demonstrating that the latter sputtering conditions could allow the fabrication of ZnSe thin films with lowest defects density and excellent flatness, suitable to be used as "window" or buffer layers within various solar cells architectures.…”
Section: Morphological Characterizationssupporting
confidence: 93%
“…According to the literature, such a grained morphology and its inhomogeneous distribution result from the use of the sputtering technique. 31 Since the oxide growth occurs perpendicularly to the Sn surface, the porous layer reflects the orientation of the metallic grain as also reported by other authors. 32 Moreover, previous works concerning studies on the growth of SnO x in alkaline media revealed the widening of the pores with prolonged anodization time.…”
Section: ■ Results and Discussionsupporting
confidence: 64%
“…Surface micrographs of obtained samples reveal a coarse inhomogeneity of morphology independent of the fabrication procedure. According to the literature, such a grained morphology and its inhomogeneous distribution result from the use of the sputtering technique . Since the oxide growth occurs perpendicularly to the Sn surface, the porous layer reflects the orientation of the metallic grain as also reported by other authors …”
Section: Resultssupporting
confidence: 53%
“…Intensity of diffraction peaks from (002) plane has enhanced with RF power due to the increase in thickness of film. As the power goes high, greater is the field strength and the number of sputtered particles increase as a result of the avalanche multiplication effect [23].…”
Section: Resultsmentioning
confidence: 99%